Homogeneous Deformation of the Gneisses of Vesterland, South-West Greenland. - Watterson, Juan (Meddelelser om Grønland, 1968)
Structural development of the migmatitic gneisses of the Vesterland area is described first by reference to successive fold episodes (F1-F3) and then by reference to the estimated pattern of three dimensional homogeneous strain. Mylonite zones, up to 2km in width, are located along at tenuated steep limbs of relatively open F3 folds. In acid gneisses F2 folds are usually isoclinal, with axial planes and axes parallel to those of F1 folds. In basic gneisses F2 folds are of relatively open style and both axes and axial planes differ from those of F1 folds. The macroscopic penetrative fabric of the gneisses is of the L-S type in which three mutually perpendicular axes can be recognised on a variety of scales, the axes corresponding to the principal axes of the strain ellipsoid. The strain ellipsoid corresponding to deformation in the acid gneisses, as estimated from the disposition of discordant acid veins, is of prolate type, with deformation path (k) approximately 17, and axial ratios 1 :3 :100. The relationship between homogeneous deformation and varying styles and attitudes of F1 and F2 folds is discussed.